THE EFFECT OF THE CONCEPT SORTING STRATEGY ON DEVELOPING CRITICAL THINKING AMONG SECOND-GRADE INTERMEDIATE LEARNERS IN SCIENCE - Researcher: Huthefa Muhamad Opeed; D.Yolla Saab (Scholars Digest Publishing, 2023)
The study aimed to find out the effect of the concept sorting strategy on developing the level of critical thinking among second grade learners average in science subject. Through the design of a teaching program based on the strategy of sorting concepts, and a test for critical thinking, prepared by the researcher. the results of the study showed that there is a statistically significant difference in the level of development of interpretation skill between the mean scores of the learners of the two groups (experimental - control) due to the strategy of sorting concepts. Statistically significant differences at the level of developing the inference skill between the mean scores of the learners of the two groups (experimental - control) attributable to the concept sorting strategy. There are also statistically significant differences at the level of developing the skill of evaluating discussions between the mean scores of the learners of the two groups (experimental - control) due to the concept sorting strategy. The study recommended training science teachers to use modern education strategies based on different theories, and holding workshops for science teachers. To train them on the concept sorting strategy, and to train them on how to develop learners' critical thinking skills.
Keywords: sorting concepts, critical thinking.